Metamorphosis of Cultural Identity of Traditional and Non-Traditional Gated Communities: A Study of Vadodara, India - Jalan Advaita (Lodz University of Technology Press, 2023)
The formation of the gated communities within and outside the walled city and western suburbs of Vadodara is influenced by the socio-cultural and socio-economic determinants respectively. The period of post-liberalization, particularly from 1991 onwards has witnessed a shift in social and economic values in society at large which has disintegrated the social construct and the concept of nuclear families have crept into Indian society vastly affecting the way housing typologies are designed and catered. This idea of modernization has transformed these traditional forms of gated communities into modern housing largely impairing the coherent urban fabric of the city, leading to irreversible process.
Keywords: gated communities; determinants; traditional; non-traditional; osiedla zamknięte; uwarunkowania; tradycyjne; nietradycyjne